THE CORRELATION BETWEEN PARENTING PARENTS’ AND STUDENTS’ MOTIVATION IN LEARNING ENGLISH ON 4rd SEMESTER AT THE FACULTY OF TEACHER TRAINING AND EDUCATION (FKIP) UNIVERSITY BATANGHARI JAMBI ACADEMIC YEAR 2016/2017 - kartika dewi (Universitas Batanghari Jambi, 2017)
Parenting parents is very important for children to provide encouragement or motivation in learning. With parenting a good influence for children, although many types of parenting applied parents’ of children dependent parents’ upbringing is applied parents to children.. The purpose in this research want to know whether there is any correlation between Parenting Parents’ and Students Motivation in learning English on43rd Semester at the Faculty of Teacher Training and Education (FKIP) University Batanghari Jambi Academic Year 2016/2017.This research is quantitative research. The population of the research is 60 students and the samples are 30 students. The data collected by questionnaire.Then, Questionnaire used Scale likert with data ordinal. The result of data questionnaire parenting the parents' highest obtained amount is 60 parents. This research, there are validity and reliability namely, validity used content validity with statement positive and negative of questionnaire and reliability the used internal consistency with formula Cronbach Alpha and correlated by used Spermant Rank correlation formula with SPPS Statistic 20. The correlation between parenting parents; and students motivation retrieved value 0,000 ˂ real level 0.025, so is mean Ho is rejected or Hi is accepted , so have correlation between parenting parents and students motivation learning English on 4rd semester at the Faculty of teacher training and education (FKIP) Batanghari University Academic Year 2016/2017. Keyword : Parenting Parents, Students Motivation in Learning English